OPTIMASI PRODUKSI USAHATANI SAYURAN ORGANIK (Studi Kasus Yayasan Bina Sarana Bakti, Cisarua, Bogor) - Muh Saiful Djafri; Harianto Harianto; Yusman Syaukat (Forum Agribisnis, 2016)
The organic farming potential is relatively large because of the high economic benefits for farmers and it is beneficial to operate. The research carried out as an idea or information to change the paradigm of organic farmers through an approach towards research on the income aspects of organic farming by production analysis. Yayasan Bina Sarana Bakti (YBSB) is the selected organic companies in the study. The objectives of this study are (1) analyze the level of organic vegetable production optimization Yayasan Bina Sarana Bakti and the level of use of resources (2) identify changes in profit in optimal conditions Yayasan Bina Sarana Bakti (3) analyze the effect of changes in prices of production inputs and outputs to the optimal production conditions. Production optimalization analysis of organic farming in view ofincome changes is aright thing to do. Linear programming analysis was used in this research. The resultsshowed that Yayasan Bina Sarana Bakti as an agribusiness company in organic vegetable production has yet to produce optimally. Optimal conditions of the company turned out to show the change in resources optimal use of resources which have not occurred on the land surplus amounted to 10.06 percent and profits at optimal conditions which is higher than the actual which profits can be increased 57,86 percent.